When illness alters drug handling: understanding pharmacokinetic changes to optimise antimicrobial dosing - Jamal, Janattul Ain (Faculty of Pharmacy, 2025)
Antimicrobials remain one of the most important drugs in modern medicine, yet their effectiveness depends greatly on how they are handled within the human body. One of the most important considerations is how pathophysiological changes during illness can profoundly reshape antimicrobial pharmacokinetics (PK). Understanding these alterations is essential not only for therapeutic success but also for preventing toxicity, resistance, and treatment failure. Therapeutic drug monitoring (TDM) and pharmacokinetic/pharmacodynamic (PK/PD) principles have become central tools in this effort. Critical illness represents a unique PK landscape. Conditions such as sepsis, shock, and major trauma alter blood flow, capillary permeability, protein binding, and organ perfusion can lead to significant PK changes, particularly on two important parameters that relate to dosing, the volume of distribution (Vd) and clearance. Mechanical ventilation, vasopressors, and renal replacement therapy (RRT) further add layers of variability.